Pengaruh Akuntabilitas dan SPI terhadap Kualitas Laporan Keuangan dengan Peran Audit Internal Sebagai Variabel Moderasi - Ardani Moresca Putu Wijaya; Dewi Saptantinah Puji Astuti (CV. ITTC INDONESIA, 2024)
This research aims to empirically examine the influence of accountability and internal control systems on the quality of financial reports with the role of internal audit as a moderating variable (survey of internal auditors at the Karisidenan Surakarta regional inspectorate office). The type of research used is quantitative research with the data source used being primary data. Data collection in this research was carried out by distributing questionnaires to internal auditors who worked at the Surakarta Karisidenan regional inspectorate office. This research used a purposive sampling type, obtaining 107 samples which were tested with SPSS 25. The results show that accountability has a significant positive effect on the quality of financial reports. The internal control system has a significant positive effect on the quality of financial reports. The role of internal audit cannot moderate the influence of accountability on the quality of financial reports. The role of internal audit cannot moderate the influence of the control system on the quality of financial reports.